Design of a Land Area Measuring Instrument Based on an STM32 and a BeiDou Positioning Chip - Wu, Xinju; Ni, Bo; Hua, Guohuan (Electronics (Basel), 2025)
This paper presents a land area measuring instrument based on an STM32 microcontroller (STMicroelectronics, Paris, France) and a BeiDou positioning chip (Zhongke Microelectronics, Hangzhou, China). The system employs BeiDou navigation as the core positioning, leveraging its unique three-track satellite cooperative networking and BDSBAS satellite-based enhancement technology as the physical layer guarantee mechanism to maintain high-precision positioning in the weak signal area of the Asia–Pacific region. At the same time, this design integrates the FreeRTOS real-time operating system to implement a dynamic memory management strategy. By adopting the linear incremental memory allocation mechanism coupled with the emergency Kalman prediction algorithm, the software layer establishes a memory buffering and fault-tolerant processing framework. Test results demonstrate a relative error below 1% in open terrains, while errors remain below 2.72% under weak signal conditions and in complex terrain environments.